2021
DOI: 10.1002/pmic.202000301
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free quantitative proteomic analysis of extracellular vesicles released from fibroblasts derived from patients with spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive disorder that represents a significant cause of infant mortality. SMA is characterized by reduced levels of the Survival Motor Neuron protein leading to the loss of alpha motor neurons in the spinal cord and brain stem as well as defects in peripheral tissues such as skeletal muscle and liver. With progress in promising therapies such as antisense oligonucleotide and gene replacement, there remains a need to better understand disease subtypes and develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…EV cargo content usually reflects the state of the cell from which they originate, and simply overexpressing a protein of interest within donor cells can lead to release of EVs loaded with high levels of that protein. 103 , 104 For example, we showed that plasmid- or adenovirus-mediated overexpression of survival motor neuron (SMN) protein in donor cells led to release of exosomes with elevated concentrations of SMN protein. 83 Countless studies have shown a similar effect with numerous different proteins.…”
Section: Engineered Ev Cargo Loading Strategiesmentioning
confidence: 99%
“…EV cargo content usually reflects the state of the cell from which they originate, and simply overexpressing a protein of interest within donor cells can lead to release of EVs loaded with high levels of that protein. 103 , 104 For example, we showed that plasmid- or adenovirus-mediated overexpression of survival motor neuron (SMN) protein in donor cells led to release of exosomes with elevated concentrations of SMN protein. 83 Countless studies have shown a similar effect with numerous different proteins.…”
Section: Engineered Ev Cargo Loading Strategiesmentioning
confidence: 99%
“…Bianchi et al analyzed the whole proteome in the CSF of 10 SMA 1 patients and 7 healthy controls (HCs) and observed 39 differentially expressed proteins between SMA patients and HCs (with APOA1, hemoglobin subunit β, hemoglobin subunit α, and transthyretin being the most significant) [48]. In extracellular vesicles released from fibroblasts of one SMA 1, two SMA 2, and three HC subjects, Roberto et al observed 116 differentially expressed proteins (with IGFBP3, Plastin 3, PTK7, TCP1, FETUA, and FXA being the most significant) [49]. Kobayashi et al analyzed nearly 1000 plasma proteins in 266 SMA patients and 22 HCs.…”
Section: Diagnosis and Prognosis Of Sma Using Molecular Biomarkersmentioning
confidence: 99%